STRATEGI GURU DALAM MENGELOLA KELAS DI KELAS III SDN 15 MAWANG MENTATAI - Nora, Rosarian; Mardiana; Akip, Muhammad (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstrack: This research aims to (1) Describe class III in class management, (2) Describe the obstacles faced by class III teachers in class management. The research questions are (1) What are the strategies of class III teachers in managing classes at SDN 15 Mawang Mentatai (2) What are the obstacles faced by teachers in managing class III in managing classes at SDN 15 Mawang Mentatai. The research was carried out in class III of SDN 15 Mawang Mentatai, Mawang Mentatai Village, Menukung District, Melawi Regency for the 2022/2024 academic year. This research uses qualitative research through observation, interviews and documentation. The subjects in this research are the principal and class III homeroom teacher, and the object of this research is the teacher's strategy in classroom management. Data collection techniques use interviews, observation and documentation. The instruments in this research are interview sheets, observation sheets and documentation. The research results show that; (1) The class teacher has carried out his role even though it is not optimal. However, the homeroom teacher still tries to achieve the goal of managing the class effectively and conducively, this can be seen from several strategies that have been implemented by the class III teacher in class management, including; First, create some creativity in making erasers from cloth that is no longer used, Second, prioritize student activity, Third, make seating arrangements, Fourth, use makeshift media in the classroom (2) The obstacles faced by class III teachers in classroom management are, First, there are still students who do not obeying the rules set by the class teacher, Second, lack of learning facilities, and Third, lack of cooperation between the class teacher and the principal to pay attention to various needs in the class. Keywords: Teacher Strategy in Classroom Management. Abstrak : Penelitian dilaksanakan di kelas III SDN 15 Mawang Mentatai Desa Mawang Mentatai, Kecamatan Menukung, Kabupaten Melawi tahun pelajaran 2022/2024. Penelitian ini menggunakan jenis penelitian kualitatif melalui observasi, wawancara,dan dokumentasi. Adapun Subjek dalam penelitian ini yaitu kepala sekolah dan wali kelas III, dan dengan objek dalam penelitian ini adalah strategi guru dalam pengelolaan kelas. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Instrumen dalam penelitian ini adalah lembar wawancara,lembar observasi dan dokumentasi. Hasil penelitian menunjukan bahwa; (1) Guru kelas sudah menjalankan perannya walaupun belum maksimal. Tetapi wali kelas tetap berusaha untuk mencapai tujuan dari pengelolaan kelas secara efektif dan kondusif,hal ini terlihat dari beberapa strategi yang telah dilakukan oleh guru kelas III dalam pengelolaan kelas diantaranya; Pertama membuat beberapa kreatifitas membuat penghapus dari kain yang sudah tidak dipakai, Kedua mengutamakan keaktifan siswa, Ketiga melakukan pengaturan tempat duduk, Keempat menggunakan media seadanya di kelas (2)Kendala yang dihadapi oleh guru kelas III dalam pengelolaan kelas yaitu Pertama masih ada siswa yang tidak mematuhi aturan yang telah ditetapkan oleh guru kelas,Kedua kurangnya sarana dalam belajar, dan Ketiga kurangnya kerjasama antara guru kelas dan kepala sekolah untuk memperhatikan berbagai keperluan di kelas. Kata Kunci:Strategi Guru Dalam Pengelolaan Kelas.